Identification and Prioritization of New Financial Provision Methods to Enhance Speed and Transparency in Financial Reporting Using the Analytic Network Process (ANP) Technique - Hamzavi, Mohamad Amin; Hematfar, Mahmoud; Basirat, Mehdi; Mahmoudi, Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The aim of this study was to identify and prioritize new financial provision methods to increase the speed and transparency of financial reporting in private banks in Iran. Method: The current research method is quantitative and survey-based. The study comprises two populations. The first population consists of 95 banking and economic managers, and the second population includes 30 academic professors with master’s and doctoral degrees in accounting, financial management, and information technology. Due to the small size of the first population, census sampling was employed, and for the second population, judgmental sampling with 25 participants was used. Data were collected through a researcher-made questionnaire and a pairwise comparison questionnaire. Findings: The findings of the study revealed that all considered variables, including payment technology, financial management technology, money transfer/remittance technology, international money transfer technology, insurtech technology, lending and crowdfunding technology, and capital market technology, are effective in enhancing the speed and transparency of financial reporting. Moreover, the findings indicated that money transfer technology, insurtech technology, international money transfer technology, capital market technology, financial management technology, lending and crowdfunding technology, and payment technology, in order of importance, have the highest significance in increasing the speed and transparency of financial reporting. Conclusion: Financial system planners can focus on prioritizing new methods of financial provision to enhance the speed and transparency of financial reporting.